Penyatuan Nilai-nilai Agama Islam dalam Pembelajaran IPS Sejarah - Sutrisno Sutrisno (Yayasan Darusssalam Bengkulu, 2020)
In the teaching of history there have been contradictions between the goal with the materials, where religion is the purpose of, but the source that comes from religion as revelation is not held as the principle of knowledge. The lessons of history lapsed diapersepsi by secular, so that there must be an effort to straighten the contradiction with the union of the values of Islam in Social Studies lessons history. This research including in descriptive explorative using naturalistic method because this research has been done on natural conditions (natural settings). Data collection techniques conducted by observation, interview, and documentation. The subject of this research is the planting of the value of the religion of Islam at MTs Miftahut Tholibin Mejobo. The object of research is in Social Studies lessons of history in class VIII, with analytically deductive analysis. The results of the study showed that the implementation ofthe values of the religion of Islam in Social Studies lessons History done by specifying the field of study which will be integrated between the Social Studies History and religion. Then, learn competency standard (SK) and basic competencies (KD) of Social Studies History with religion and identify some basic competency in various SK that has potency to be united. The superiority of this learning can improve student learning motivation and increase cooperation between subject and teachers. The disadvantages are the limitations of social studies teachers about the history of the understanding of the arguments of the Qur'an and Hadith and there is no manual book that brings together the subjects with the values of Islam.